Inhibition of Endogenous NGF Degradation Induces Mechanical Allodynia and Thermal Hyperalgesia in Rats. (29th July 2013) - Osikowicz, Maria; Longo, Geraldine; Allard, Simon; Cuello, A Claudio; Ribeiro-da-Silva, Alfredo
Background: We have previously shown a sprouting of sympathetic fibers into the upper dermis of the skin following subcutaneous injection of complete Freund's adjuvant (CFA) into the hindpaw. This sprouting correlated with an increase in pain-related sensitivity. We hypothesized that this sprouting and pain-related behavior were caused by an increase in nerve growth factor (NGF) levels. In this study, we investigated whether the inhibition of mature NGF degradation, using a matrix metalloproteinase 2 and 9 (MMP-2/9) inhibitor, was sufficient to reproduce a similar phenotype. Results: Behavioral tests performed on male Sprague-Dawley rats at 1, 3, 7 and 14 days after intra-plantar MMP-2 /9 inhibitor administration demonstrated that acute and chronic injections of the MMP-2/9 inhibitor induced sensitization, in a dose dependent manner, to mechanical, hot and cold stimuli as measured by von Frey filaments, Hargreaves and acetone tests, respectively. Moreover, the protein levels of mature NGF (mNGF) were increased, whereas the levels and enzymatic activity of matrix metalloproteinase 9 were reduced in the glabrous skin of the hind paw. MMP-2/9 inhibition also led to a robust sprouting of sympathetic fibers into the upper dermis but there were no changes in the density of peptidergic nociceptive afferents. Conclusions: These findings indicate that localized MMP-2/9 inhibition provokes a pattern of sensitization and fiber sprouting comparable to that previously obtained following CFA injection. Accordingly, the modulation of endogenous NGF levels should be considered as a potential therapeutic target for the management of inflammatory pain associated with arthritis.